Great Scots. (Edinburgh : Trustees of the National Galleries of Scotland)
Adam Robert ; Adam, William ; Ancram, Robert Kerr ; Barrie, James Matthew ; Boswell, James ; Bothwell, James Hepburn ; Bruce, James ; Bruce, Sir William ; Burns, Robert ; etc.
boek